Analisis ameloblastoma unilokuler menggunakan radiograf cone beam computed tomography (CBCT) 3D sebagai penunjang diagnosis - Siska Damayanti Saifuddin; Farina Pramanik; Ria Noerianingsih Firman (Ikatan Radiologi Kedokteran Gigi Indonesia, 2019)
Objectives: This purpose of this case report is to explain the imaging characteristics of unilocular ameloblastoma in CBCT 3D radiograph. Case Report: A 32-year-old male patient came to the dentist complaining his painful right lower jaw over the past few days. Clinical examination showed extensive swelling in the posterior region of the right mandible to cause asymmetry at the inferior border of the mandibular corpus. Panoramic radiography showed radiolucent area in periapical mesial root of 46 tooth, extending to the right angular mandibular with a clearly demarcated shape, and there was a root resorption of 47 tooth. CBCT 3D examination showed the presence of unilocular radiolucent lesion in a regular shape and a clear borderline, extending to the inferior border of the mandible and causing buccal-lingual cortical perforation accompanied with the resorption of adjacent 47 tooth. Conclusion: CBCT is a supporting radiography that may act as a more accurate diagnostic tool for the diagnosis of unique ameloblastoma lesions.